Microwave assisted biodiesel production using a novel Brønsted acid catalyst based on nanomagnetic biocomposite. (15th June 2019) - Chellappan, Suchith; Aparna, K.; Chingakham, Ch.; Sajith, V.; Nair, Vaishakh
Graphical abstract: Highlights: Novel nanomagnetic biocomposite catalyst for biodiesel production. The usage of cassava peel biowaste for biochar production. Incorporation of nanomagnetic particles helps in easy recovery and high surface area of catalyst. The properties of the biodiesel produced were found to meet international standards. Abstract: In the present study, a novel magnetic sulfonated solid acid catalyst was synthesized using cassava peel, a biomass waste, by incorporating Fe3 O4 nanoparticles. The cassava peel biochar was prepared by slow pyrolysis which was further sulfonated with concentrated H2 SO4 . The magnetic Fe3 O4 nanoparticles synthesized by co-precipitation method was incorporated in the sulfonated biochar by ultrasonication to obtain a magnetized sulfonated biochar catalyst. Fe3 O4 nanoparticles give excellent stability as the acid sites on the shell structure are easily accessible to reactant sites and also aids in the separation of the catalyst after the transesterification process. The characterization results confirmed that magnetized sulfonated biochar catalyst contains three functional acidic sites: weak (OH) and strong (COOH and SO3 H) acidic groups. The catalytic activity and reusability of the magnetic biocatalyst were investigated by microwave assisted biodiesel production from Millettia pinnata seed oil. The biodiesel yield of 98.7% was obtained under the optimum parametric conditions. The enhanced stability and activity of the magnetic catalyst are due to the strong ionic interactions between particles, high sulfonic acid group density and higher accessibility of reactants towards acidic sites. The reusability of catalyst was studied by using it for five cycles obtaining a yield of more than 75%. The fuel properties of the synthesized biodiesel were found to meet international biodiesel standards.